Impact of Financial Development on Real Income Dynamics - Cyprian S. Anyalagbu; Anne Chinonye Maduka; Ogonna Emmanuel Ifebi; Collins Bruno Ibekilo (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study investigates the impact of financial development on economic growth across 20 Sub-Saharan African countries from 2007 to 2024. Grounded in an augmented Solow growth framework, the research incorporates human capital and financial development as key determinants of output. To address endogeneity and unobserved heterogeneity, the authors utilized the System Generalized Method of Moments (SGMM) estimator. Preliminary diagnostics, including the Bond (2002) test, justified this approach by identifying bias patterns in OLS (0.5232) and Fixed Effects (-0.3533) estimations. Additionally, Pesaran (15.003, p=0.0000) and Friedman (85.631, p=0.0000) tests confirmed the presence of cross-sectional dependence that required control within the model. The empirical findings reveal that financial development impacts real income through distinct and sometimes conflicting channels. Financial institution access (0.163, p<0.05) and institutional quality (0.674, p<0.05) were found to have significant positive effects on economic growth. Conversely, the results indicate that financial market depth (-0.249, p<0.05) has a negative impact on growth, while financial efficiency (-0.049) remains statistically insignificant. Diagnostic checks, including Hansen (0.289) and AR(2) (0.331) tests, confirmed the validity and reliability of these results. Consequently, the study concludes that financial development affects growth unevenly across its channels. The authors recommend that policymakers focus on improving financial inclusion and strengthening institutional frameworks while exercising caution regarding the deepening of debt markets.